PRODUCTIVITY AND FEASIBILITY OF CATCHING BUSINESS WITH CATCHING BOAT BOAT AT THE BUNGUS OCEAN FISHING PORT WEST SUMATRA - Sukmawati Sukmawati; Bustari Bustari; Nofrizal Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract This study aims to determine the value of productivity and feasibility of fishing with boat lift gear at the Bungus Ocean Fishing Port, West Sumatra. The research method used in this study is a survey method,and data analysis was done by descriptive analysis. The analysis carried out is productivity analysis and financial analysis. The results showed that the average productivity of the ship was IDR. 11,206,455, - per GT with the highest productivity value for productivity per GT in 2020, which was IDR. 18,844,333,- per GT. As for productivity per trip the average ship is IDR. 29,558,618,- per trip with the highest productivity value for productivity per trip of IDR.47,258,000,- per trip. The highest productivity per crew member is IDR 47.258.000,- per crew member. Analysis of economic efficiency on sample vessels shows that the efficiency value of capture fisheries business with boat lift fishing gear with small and large ship sizes can be said to be efficient. This can be seen from the efficiency value of these vessels, which is worth 1. However, the fishing effort with boat lift gear as a whole can be said to be efficient with an average efficiency value of 1.573. This indicates that the fishing effort using the lift net fishing gear carried out by fishermen at the Bungus Ocean Fishing Port, West Sumatra is feasible to develop because of its efficiency value 1.Keywords: Boat Charts, Financial Analysis, Productivity